2013
DOI: 10.1186/1471-2202-14-59
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the endothelial blood-CNS barriers: a method for the production of robust in vitromodels of the rat blood-brain barrier and blood-spinal cord barrier

Abstract: BackgroundModelling the blood-CNS barriers of the brain and spinal cord in vitro continues to provide a considerable challenge for research studying the passage of large and small molecules in and out of the central nervous system, both within the context of basic biology and for pharmaceutical drug discovery. Although there has been considerable success over the previous two decades in establishing useful in vitro primary endothelial cell cultures from the blood-CNS barriers, no model fully mimics the high el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 93 publications
(111 reference statements)
4
81
0
Order By: Relevance
“…Likewise, bEnd.3 cells presented a characteristic spindle-shaped morphology (Mühlner et al, 1999;Sheibani and Frazier, 1995). Importantly, the presence of continuous and organized tight and adherens junctions, known to be required for the proper BBB functioning Martins et al, 2013;Watson et al, 2013), was observed in the interendothelial cell contact. These data support the establishment of a highly restrictive barrier.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Likewise, bEnd.3 cells presented a characteristic spindle-shaped morphology (Mühlner et al, 1999;Sheibani and Frazier, 1995). Importantly, the presence of continuous and organized tight and adherens junctions, known to be required for the proper BBB functioning Martins et al, 2013;Watson et al, 2013), was observed in the interendothelial cell contact. These data support the establishment of a highly restrictive barrier.…”
Section: Discussionmentioning
confidence: 96%
“…Transendothelial flux test was adapted from a protocol described by Watson and co-workers (Watson et al, 2013). The test was performed after 11 days of bEnd.3 cells and astrocytes coculture.…”
Section: Transendothelial Fluxmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, all cell-based systems require specifi c growth surface coatings and cell culture media for growing BECs. Although the cell preparations and culture conditions are all based on the same principle, in order to obtain functional in vitro BBB models several small but signifi cant differences between the systems, as well as preferences between laboratories have been introduced (Garberg 1998 ;de Boer and Sutanto 1997 ), an ongoing process as shown by recent papers (Abbott et al 2012 ;Patabendige et al 2013b ;Watson et al 2013 ). In the following sections current in vitro models of the BBB are briefl y surveyed; for greater detail on specifi c systems the reader is referred to the corresponding key publications.…”
Section: Current Status: Overview Of Current In Vitro Bbb Modelsmentioning
confidence: 98%